Fabrication and evaluation of polymeric membranes for blood dialysis treatments using functionalized MWCNT based nanocomposite and sulphonated-PES - Irfan, M. (Royal Society of Chemistry, 2016)
The use of polyethersulfone (PES) based membranes for dialysis therapy is increasing, but the transformation and adsorption of blood proteins, destruction of red blood cells, and thrombosis responses against PES membrane can raise severe blood reactions affecting the rate of morbidity and mortality of hemodialysis (HD) patients. In this work, the performance and biocompatibility of PES membranes were improved by sulfonation and nanocomposites (NCs) additives. Acid functionalized multiwall carbon nanotubes (f-MWCNT) and polyvinylpyrrolidone (PVP) were used for NCs preparation and then they were incorporated into sulfonated-polyethersulfone (S-PES) based membranes. The hydrophilic part of f-MWCNT contributed to the -COOH and -OH groups, whereas sulfonated polymer provided the -SO2H group in the membrane composition. The formulated HD membranes were characterized by FTIR, FESEM and contact angle. The AFM was used for the estimation of the surface roughness and surface profile studies, whereas flux rate, and rejection rate was also determined. The biocompatibility results revealed that sulfonated-NCs based membranes had reduced 55% (BSA), 65% (lysozyme) adsorption and 74.80% hemolysis process. It also demonstrated higher clotting time of prothrombin (PT), thrombin (TT), activated partial thrombin time (APTT), plasma re-calcification time (PRT). The dialysis results indicated that, compared to the pristine PES membrane, the clearance ratio of lysozyme, urea and creatinine solutes increased up to 32.4%, 59.2% and 57.3%, respectively. Thus, the blending of S-PES and NCs in the PES membrane highly improved the biocompatibility and removal ability of uremic solutes.